2000
DOI: 10.4049/jimmunol.164.1.283
|View full text |Cite
|
Sign up to set email alerts
|

Conserved MHC Class I Peptide Binding Motif Between Humans and Rhesus Macaques

Abstract: Since the onset of the HIV pandemic, the use of nonhuman primate models of infection has increasingly become important. An excellent model to study HIV infection and immunological responses, in particular cell-mediated immune responses, is SIV infection of rhesus macaques. CTL epitopes have been mapped using SIV-infected rhesus macaques, but, to date, a peptide binding motif has been described for only one rhesus class I MHC molecule, Mamu-A*01. Herein, we have established peptide-live cell binding assays for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
0
1

Year Published

2000
2000
2007
2007

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 50 publications
(50 citation statements)
references
References 57 publications
2
47
0
1
Order By: Relevance
“…General motifs crucial for high affinity binding for five different Mamu class I molecules (A*01, A*11, B*03, B*04, and B*17) were also identified (5). The utility of this approach was emphasized by a recent study in which 27 new SIV-derived A*01-restricted epitopes were revealed, based on sequence motif and Mamu A*01 in vitro binding assays using purified MHC molecules.…”
Section: S Imian Immunodeficiency Virus-infected Rhesus Macaquesmentioning
confidence: 95%
See 1 more Smart Citation
“…General motifs crucial for high affinity binding for five different Mamu class I molecules (A*01, A*11, B*03, B*04, and B*17) were also identified (5). The utility of this approach was emphasized by a recent study in which 27 new SIV-derived A*01-restricted epitopes were revealed, based on sequence motif and Mamu A*01 in vitro binding assays using purified MHC molecules.…”
Section: S Imian Immunodeficiency Virus-infected Rhesus Macaquesmentioning
confidence: 95%
“…Future studies will be needed to determine whether this finding can be extended as a generalization for Mamu class I alleles. Interestingly, the one and only optimal epitope thus far identified for Mamu A*11 is indeed an 8-mer (5,50). Additional analyses are necessary to determine whether shorter (7 residues), or longer (12 residues or above) peptides also bind Mamu A*01 with appreciable frequency.…”
Section: Discussionmentioning
confidence: 99%
“…Peptide binding to equine MHC class I molecule 7-6 expressed on transduced 721.221 cells was measured as previously described with minor modifications (41,46,47). 721.221 cells (2 ϫ 10 6 /ml) transduced with equine classical MHC class I gene 7-6 or with a retroviral vector that did not express an equine gene were preincubated overnight in RPMI with 15% FBS and 3 g/ml of human ␤ 2 -microglobulin (The Scripps Clinic, La Jolla, CA) at 27°C.…”
Section: Live Cell Peptide Binding Assaymentioning
confidence: 99%
“…Peptides used were synthesized at Epimmune (San Diego, CA) as described elsewhere (44) or were purchased as crude material from Mimotopes (Minneapolis, MN). Peptides synthesized at Epimmune were typically purified to Ͼ95% homogeneity by reverse-phase HPLC.…”
Section: Peptide Synthesis and Radiolabelingmentioning
confidence: 99%